The role of ENSO flavours and TNA on recent droughts over Amazon forests and the Northeast Brazil region - Jimenez, JC; Marengo, JA; Alves, LM; Sulca, JC; Takahashi, K; Ferrett, S; Collins, M (International Journal of Climatology, 2019)
This is the author accepted manuscript Amazon tropical forests and the semiarid Northeast Brazil (NEB) region have registered very severe droughts during the last two decades, with a frequency that may have exceeded natural climate variability. Severe droughts impact the physiological response of Amazon forests, decreasing the availability to absorb atmospheric CO2, as well as biodiversity and increasing risk of fires. Droughts on this region also affect population by isolating them due to anomalous low river levels. Impacts of droughts over NEB region are related to water and energy security and subsistence agriculture. Most drought episodes over Amazonia and NEB are associated with El Niño (EN) events, anomalous warming over the Tropical North Atlantic (TNA), and even an overlapping among them. However, not all the dry episodes showed a large-scale pattern linked to a canonical EN event or warm TNA episodes. For instance, dry episodes linked to EN events present distinct spatial patterns of precipitation anomalies depending on EN type (Central-Pacific vs. Eastern-Pacific EN), and NEB region experienced a severe drought in 2012 that is not attributed to EN or warm TNA events. Even in the case of the strong EN in 2015/16, some regional impacts have not been explained by EN contribution. This paper discusses the effects of CP and EP EN events, and the role of warm TNA events on tropical Walker and Hadley circulation leading to drought over Amazonia and NEB regions. Natural Environment Research Council (NERC)